Rôle des métaphores verbales et gestuelles dans le développement de la prudence lors d’activités de dialogue philosophique - Sandra Lagrange-Lanaspre (Éducation et Socialisation)
This paper addresses the role of philosophical practice in the development of Aristotelian phronesis to enable younger generation to cope with human vulnerabilities. We study two sessions of philosophical practice involving eleven- and twelve-years old pupils of an educational priority area middle school in Grenoble, France. These activities are inspired by the Lipman’s approach of Community of Philosophical Inquiry and the Tozzi’s one of democratic and philosophical discussion. Extending our previous research, we investigate more specifically phenomena we refer to as "bimodal metaphorical philosophemes". We define them as sequences of recurring verbal and gestural metaphors that facilitate the co-construction of definitions during philosophical discussions. We show that bimodal metaphorical philosophemes foster the development of phronesis in pre-teens involved in the philosophical discussions we study. In this way, philosophical practices may help future generations cope with human vulnerabilities in the sense described by Cynthia Fleury.